Bilingual learning implementation and english language mastery of preschoolers in TK My Liberty - Rahmawati Nur Alim (Indonesian Reseacher for Language Learning and Teaching, 2024)
ABSTRACT This qualitative research reviews the implementation of bilingualism in the teaching/learning activities and mastering English language in early childhood setting. It emphasizes the urgency of language in children's language and cognitive development. All data were collected from observations, documentations, and interviews with teachers and the school principal in TK My Liberty. Research findings indicate that the implementation of English curriculum is central to bilingual learning that can be integrated in planning, implementation, and evaluation processes. The present work also finds four basic English language learning aspects implemented in TK My Liberty Kids School: vocabulary, reading, writing, and speaking. On top of that, teachers' roles are central to the success of the English mastery. Using appropriate media is one of the best strategies in Bilingualism learning activity. It furthers the progress of preschoolers to master all of English skills in early age. In conclusion, the implementation of bilingual program has positive impact on children's language and cognitive development, encompassing aspects of the mastery the foreign language, namely vocabulary, reading, writing and speaking. Nevertheless, it should be noted that the implementation requires improvement due to less optimum results in some aspects. Keyword: Bilingual Learning, English Language, Preschoolers